(untitled) (مجلة المنصور, 2023)
Most programs needed to be written in a way that are aware of the existence of each other and which can co-operate with each other towards some common goal. The standard solution to this problem is interprocess communication mechanisms (IPC). Any IPC mechanism is chosen, there is still the context switch overhead to contend with whenever normal processes need to work together. The way to overcome this is to use the concept of threads. The idea behind threads is that each process can have its processor time slices shared between several concurrent threads, each of which also shares the memory and data structures of the process to which it belongs. In this paper a new and simple user level threads library is presented. This library can be easily used by the programmers to gain the benefits of threads. As an application a solution to the unbounded buffer problem is implemented using the developed thread library. C language under Linux Operating system is used for programming.